2019
DOI: 10.1002/slct.201803926
|View full text |Cite
|
Sign up to set email alerts
|

Renewable‐Resource‐Based Waste Materials for Supercapacitor Application

Abstract: Herein, renewable resource‐based waste materials (used tea leaves and molasses) were utilized as inexpensive and renewable carbon sources to develop Phosphorus and Nitrogen co‐doped Carbon (PNDC) materials for supercapacitor application. A prompt, low cost, single step, green and facile microwave assisted process was utilized to prepare PNDC materials using the aforementioned biomass. Concentration of the doping elements (P and N) was altered in the resulting PNDC materials by varying the mole ratio of used te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…PNDC and SiPNDC were prepared via a microwave-assisted technique reported elsewhere [27,37,38]. To prepare SiPNDC, a 2.0 g sample of molasses was blended well in a mortar and pestle with APP (1.2 g) and 0.6 g PDMS.…”
Section: Materials and Synthesismentioning
confidence: 99%
“…PNDC and SiPNDC were prepared via a microwave-assisted technique reported elsewhere [27,37,38]. To prepare SiPNDC, a 2.0 g sample of molasses was blended well in a mortar and pestle with APP (1.2 g) and 0.6 g PDMS.…”
Section: Materials and Synthesismentioning
confidence: 99%
“…Waste CFs were collected from receptacles located around UA Little Rock campus and carbonized through a facile, low-cost, microwave-assisted method described previously [22]. For DCCF synthesis, the CFs were weighed and combined with APP in a mass ratio of 1:0.4 g, and 2 drops of water was added to help initiate microwave carbonization process.…”
Section: Adsorbent Synthesismentioning
confidence: 99%
“…The specific capacitance and surface area were found to be 161 F/g and 433 m 2 /g, respectively. We also used different precursors to produce doped nitrogen and phosphorous carbon using microwave technology to achieve materials with high specific capacitance values (182 F/g) [173,174]. It has been observed that microwave technique usually produces high surface area materials [167].…”
Section: Co-doped Materialsmentioning
confidence: 99%